Obesity and adult asthma: diagnostic and management challenges. Issue 1 (January 2019) - Grace, Jon; Mohan, Arjun; Lugogo, Njira Lucia
Abstract : Purpose of review: Despite advances in our understanding of the obese asthma phenotype, heterogeneity and large gaps in knowledge have hindered significant advances in directed interventions. Recent findings: Obesity is associated with poorer asthma-related outcomes and increased risk of progression to severe asthma. Obese asthma is associated with variability in the expression of inflammatory markers, lung function impairments, and response to conventional and biologic therapies. In addition, traditional asthma biomarkers are not as reliable in obese patients. Several mechanistic pathways that uniquely impact asthma in obesity have been identified. Pathways involving innate lymphoid cells (ILC) type 2 (ILC-2) cells, surfactant protein-A, cell division control protein (CDC)42, interleukin (IL)-6, IL-17, and IL-33 are likely causal inflammatory pathways. Obesity also confounds lung function parameters making accurate diagnosis more challenging. As such, personalized asthma therapies directed towards obese asthma endotypes remain elusive. Summary: Obesity confounds traditional asthma biomarkers and lung function measurements, thus defining obese asthma endotypes remains challenging. Novel pathways are being identified and hold promise for future targeted therapies. However, we are in dire need of updated guidelines regarding asthma diagnosis in obese patients and the development of biomarkers that more accurately identify specific endotypes.